Oxygen Saturation in Severe Malnutrition - Salahuddin, Muhammad; Mustafa, Sultan; Masood, Shaheen; Mumtaz, Sana; Ali Shah, Muhammad; Ali, Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Severe malnutrition remains a major cause of childhood morbidity and mortality in low- and middle-income countries. Hypoxemia is a strong predictor of mortality, yet it is often underrecognized in malnourished patients. Objective: To assess oxygen saturation levels in patients with severe malnutrition and to determine associated clinical factors, including pneumonia and anemia. Methodology: This cross-sectional analytical study was conducted at Abbasi Shaheed Hospital, Karachi, from February 1, 2024, to January 31, 2025. A total of 185 patients with severe malnutrition, as defined by World Health Organization criteria, were enrolled using a non-probability consecutive sampling method. Oxygen saturation was measured using a standardized pulse oximeter at the time of admission. Demographic and clinical data, including the presence of anemia and pneumonia, were recorded. Results: The mean age of participants was 3.8 ± 1.6 years, with 55.1% males and 44.9% females. Marasmus was present in 59.5% of cases, while 40.5% had kwashiorkor. The mean oxygen saturation at admission was 91.4% ± 4.2. Hypoxemia (SpO₂ <90%) was observed in 33.5% of patients. Children with pneumonia demonstrated significantly higher rates of hypoxemia compared to those without pneumonia (47.8% vs. 24.2%, p = 0.01). Anemia was also significantly associated with low oxygen saturation (39.7% vs. 21.9%, p = 0.03). Younger children (<2 years) showed a higher prevalence of hypoxemia (40.0%) compared to older age groups. Conclusion: It is concluded that hypoxemia is frequent among patients with severe malnutrition, particularly in those with pneumonia, anemia, and younger age. Routine pulse oximetry should be integrated into the assessment of malnourished patients to enable early detection and timely oxygen therapy. Addressing coexisting infections and anemia alongside nutritional rehabilitation may reduce preventable mortality.